Impact of Country of Origin on Consumer Buying Behaviour: In Context to Foreign Retail Companies in India - Gupta, Vidit (2012)
The global business environment has witnessed the unprecedented growth and development of multinational and transnational organization. The internationalization thus, became the undisputed truth of modern societies as consumers seek to source their needs from the cross border trade activities. However, there have been many studies that discussed that specific countries are known for their specific competitive advantages in terms of technology, resources, innovation and other source of product differentiation. Such studies unleashed the new phenomenon called ‘country of origin’ which suggested that perceived image of country has significant impact on the purchasing decisions of the consumers. Retail sector in India recently witnessed unprecedented growth, development and presence of various foreign brands ranging from automobiles to grocery, apparels and electronics. However, most foreign companies used product differentiation strategy and suitable marketing mix to gain competitive advantage in terms of raising their market share but the study looked forward to identify the benefits of foreign brands perceived by Indian consumers. The report further looked forward to identify the buying traits and driver of consumers towards foreign brands. The primary and secondary findings suggested that marketing mix, brand image, brand familiarity and equity, past experience, word of mouth promotion, travelling abroad are some of the factors that influence the consumers towards foreign brands. The findings from theoretical analysis found that some companies emphasized on conveying COO image through various marketing communication channels and brand message strategy. Though, primary data findings discussed that other marketing initiatives like online marketing strategy, physical evidence of services, effective branding and improvement in core competencies and capabilities can further help companies to reinforce consumer behaviour. The secondary data was collected using various academic, digital and media sources including text books, journals, articles and library sources whereas primary data was collected using the structured face to face interview method on the shoppers visited at major shopping malls in New Delhi.